Management of Postoperative Delirium in Elderly: A Narrative Literature Review - Victor Pulpa Seda (HM Publisher, 2021)
Postoperative delirium can occur in people undergoing surgery at any age but is more common in older people. The causes of postoperative delirium are not fully understood but are thought to be related to the side effects of anesthetic drugs, stress from surgery, and hormonal and biochemical changes in the body due to surgery. This literature review aimed to describe the management of postoperative delirium in the inpatient age. One of the factors that influence the occurrence of postoperative delirium is systemic inflammation that occurs due to physiological stress and local inflammation that occurs during surgery. Systemic inflammation can trigger an exaggerated immune response in the body, producing proinflammatory cytokines that can affect brain and nerve function. Postoperative management of patients with delirium must be based on the underlying cause and the symptoms experienced by the patient. Once delirium symptoms are under control, patients should be recovered with appropriate rehabilitation and treatment, including physical therapy and occupational therapy, to help improve their physical and cognitive function. In conclusion, the management of postoperative delirium aims to reduce delirium symptoms and restore the patient's cognitive function as quickly as possible so that the patient can recover optimally and avoid more serious complications.